Eradication of Lantana, eupatorium and Other Pests - Lal, K. B. Mohan (Indian Forester, 1960)
In Khasi-Jaintia Hills Lantana, Eupatorium lands are cultivated for potato, vegetables, rice, maize etc. Their method of cultivation is not only helpful in eradication of these pests but these are used for disinfecting and enriching the soil by slow burning under cover of earth. This method of cultivation is being used to grow pine and wattle by taungya method. It is suggested that in the plain areas sissoo which has been a difficult species in plantations may be grown by this method. For eradication of herbaceous pests making them into compost is suggested and a suitable method for the same is outlined.